2019
DOI: 10.1126/science.aav4313
|View full text |Cite
|
Sign up to set email alerts
|

Shifting habitat mosaics and fish production across river basins

Abstract: Watersheds are complex mosaics of habitats whose conditions vary across space and time as landscape features filter overriding climate forcing, yet the extent to which the reliability of ecosystem services depends on these dynamics remains unknown. We quantified how shifting habitat mosaics are expressed across a range of spatial scales within a large, free-flowing river, and how they stabilize the production of Pacific salmon that support valuable fisheries. The strontium isotope records of ear stones (otolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 38 publications
4
92
0
Order By: Relevance
“…The opposite was true in the Little Colorado River, characterized by low mainstem hydrologic connectivity, where perennial streams had more unique species composition. Despite the fact that the strength of our inferences are limited by including just two basins for comparison, these findings support the long recognized value of complementarity in conservation planning (Brennan et al, ; Vane‐Wright, Humphries, & Williams, ).…”
Section: Discussionsupporting
confidence: 51%
“…The opposite was true in the Little Colorado River, characterized by low mainstem hydrologic connectivity, where perennial streams had more unique species composition. Despite the fact that the strength of our inferences are limited by including just two basins for comparison, these findings support the long recognized value of complementarity in conservation planning (Brennan et al, ; Vane‐Wright, Humphries, & Williams, ).…”
Section: Discussionsupporting
confidence: 51%
“…Highland water samples displayed distinct 87 Sr/ 86 Sr than those from midelevation (yunga) and coastal zones, which demonstrates the homogenization of water strontium sources as rivers drain into the Pacific Ocean. Heterogeneity in water 87 Sr/ 86 Sr increases with watershed size, a finding that differs from the findings of Brennan et al (2019). In the Andes, the largest watersheds are located along the eastern slopes of the Andes and the Amazon Rainforest (Figure 2).…”
Section: Discussionmentioning
confidence: 67%
“…Hodell et al (2004) report that water body depth also influences 87 Sr/ 86 Srlocations with shallower water tables reflect upstream mixing, while locations with deeper water tables reflect more of the underlying bedrock signature. Watershed size also influenced 87 Sr/ 86 Sr variability, with larger watersheds leading to more homogenized 87 Sr/ 86 Sr in rivers (Brennan et al, 2019).…”
Section: Assessing Water As a Proxy For Local Skeletal 87 Sr/ 86 Srmentioning
confidence: 99%
See 1 more Smart Citation
“…Terui et al () showed that increased branching complexities of stream networks stabilised temporal metapopulation sizes of several fish species. Negative covariation in local vital rates likely enhances a portfolio effect (Schindler et al , Brennan et al ) in spatially structured populations. In fact, such an effect may be amplified by habitat heterogeneity among habitat patches.…”
Section: Discussionmentioning
confidence: 99%